Human-Centered Design Science Research Evaluation for Gamified Augmented Reality - Vasilevski, Nikolche; Birt, James (Frontiers in Virtual Reality, 2021)
As augmented reality (AR) and gamification design artifacts for education proliferate in the mobile and wearable device market, multiple frameworks have been developed to implement AR and gamification. However, there is currently no explicit guidance on designing and conducting a human-centered evaluation activity beyond suggesting possible methods that could be used for evaluation. This study focuses on human-centered design evaluation pattern for gamified AR using Design Science Research Methodology (DSRM) to support educators and developers in constructing immersive AR games. Specifically, we present an evaluation pattern for a location-based educational indigenous experience that can be used as a case study to support the design of augmented (or mixed) reality interfaces, gamification implementations, and location-based services. This is achieved through the evaluation of three design iterations obtained in the development cycle of the solution. The holistic analysis of all iterations showed that the evaluation process could be reused, evolved, and its complexity reduced. Furthermore, the pattern is compatible with formative and summative evaluation and the technical or human-oriented types of evaluation. This approach provides a method to inform the evaluation of gamified AR apps. At the same time, it will enable a more approachable evaluation process to support educators, designers, and developers.